Побудова спектральних моделей сигналів в різних теоретико числових базисах та представлення їх в полярній системі координат - Сегін, А. І. (Vinnytsia National Technical University, 2015)
The theoretical basis of spectral characteristics of the signal in the polar coordinate system. A comparative analysis of analytical and graphical representation of the typical signals in rectangular and polar coordinates. It is proved the feasibility of the implementation of the spectral analysis of the signal in the polar coordinate system, which provides simplification of the calculations, due to a simple analytical representation of harmonic signals. It is shown that the graphical representation of the spectral characteristics of the signals in the polar coordinates system in comparison with a rectangular, more clearly and better reflect the physical meaning. The spectrum of periodic signals on the entire interval of observation can be easily displayed in a confined space without performing scaling. It is proposed to calculate the spectral pattern signal not only the basis of Fourier, but other number-theoretic bases such as Christenson and Rademacher that for certain classes of signals provide better convergence.